Semantic Structure Of The Word - Kurbonova Matluba; Sobirova Mohira; Usmonova Madina (Zien Journals, 2022)
The article deals with the problem of the word in the science of linguistics, the structure of the word in languages of different systems and at different stages of language development, the semantic structure of the word. The question of some external - mainly phonetic or internal - grammatical or lexical-semantic features of the word is being resolved
Keywords: Problem; language; linguistics; evolution